Cognitive performance determinants in competitive fencing: a systematic review - Ade Zalindro; Rudyanto Rudyanto; M. Arie Desman (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
Competitive fencing is an open-skill combat sport in which perception, anticipation, decision-making, and action occur under severe temporal pressure. This review synthesised evidence on cognitive performance determinants in fencing, with emphasis on sport-specific anticipation and visual attention, reaction and response selection, and trainability. A structured Scopus search was conducted in accordance with PRISMA 2020 and identified 403 records; 15 duplicates were removed, 388 titles and abstracts were screened, 70 full texts were assessed, and 18 studies were included. Eligibility was defined using a PICOS framework, and study quality and relevance were appraised with a prespecified four-domain FICO rubric (Focus, Information, Context, Outcome). Because the included studies used heterogeneous designs and non-comparable outcome operationalisations, evidence was synthesised narratively and thematically following the Thomas and Harden approach rather than quantitatively pooled. The evidence indicates that expertise is expressed primarily through sport-specific anticipation, weapon-dependent visual search, and efficient response selection and inhibition, whereas generic simple reaction time is less discriminative. Training interventions improved attention or broader cognitive function, but transfer to isolated reaction-time outcomes was inconsistent. The current screening record does not contain a reproducible inter-rater agreement statistic; accordingly, no Cohen's kappa value is reported without verification. Larger longitudinal studies, standardised fencing-specific measures, and ecologically valid designs are needed.